2015
DOI: 10.1186/s12862-015-0490-2
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and adaptive evolution of the gibberellin oxidase genes in plants

Abstract: BackgroundThe important phytohormone gibberellins (GAs) play key roles in various developmental processes. GA oxidases (GAoxs) are critical enzymes in GA synthesis pathway, but their classification, evolutionary history and the forces driving the evolution of plant GAox genes remain poorly understood.ResultsThis study provides the first large-scale evolutionary analysis of GAox genes in plants by using an extensive whole-genome dataset of 41 species, representing green algae, bryophytes, pteridophyte, and seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 109 publications
3
50
0
1
Order By: Relevance
“…Comparison of FveGA20ox4 with other GA20ox from Arabidopsis indicated that the deletion was within the predicted catalytic domain of the enzyme Huang et al, 2015), thus possibly affecting its activity (Supplemental Figure 3B). GA20ox enzymes catalyze several reactions in the GA biosynthetic pathway to produce precursors that are further converted into bioactive GAs by subsequent enzymes in the pathway ( Figure 6A).…”
Section: Fvega20ox4 Is Strongly Expressed In the Axmmentioning
confidence: 99%
“…Comparison of FveGA20ox4 with other GA20ox from Arabidopsis indicated that the deletion was within the predicted catalytic domain of the enzyme Huang et al, 2015), thus possibly affecting its activity (Supplemental Figure 3B). GA20ox enzymes catalyze several reactions in the GA biosynthetic pathway to produce precursors that are further converted into bioactive GAs by subsequent enzymes in the pathway ( Figure 6A).…”
Section: Fvega20ox4 Is Strongly Expressed In the Axmmentioning
confidence: 99%
“…Motif 14 overlaps the KLPWKETLS domain of GA20OXs, which is considered to define affinity for GA 12 and GA 53 (Xu et al, 1995;Sakamoto et al, 2004). Parts of both motifs 4 and 14 overlap a stretch of sequence characterized as being functionally divergent and under positive selection in GA3OX proteins (Huang et al, 2015). A number of studies have also observed the C-terminal tail (i.e., GA3OX motif 18), to exert important control over 2ODD enzyme activity.…”
Section: Sufficient Differences Exist Between Wheat and Wild Radish Gmentioning
confidence: 99%
“…RrGA3OX1a and RrGA3OX2a CDS and protein sequences have been deposited into National Center for Biotechnology Information (NCBI) database; accession numbers (KP271966) and (KP271967) respectively. GA3OX, GA20OX, and GA2OX sequences across the angiosperms were obtained partially from (Huang et al, 2015) with additional sequences identified with BLASTp at NCBI using Arabidopsis and rice GAOX sequences as queries. R. raphanistrum genomic and predicted protein sequences were mined from RadishDB: http://radish.…”
Section: Protein Sequences and Phylogeniesmentioning
confidence: 99%
“…Along with the biosynthetic enzymes, the third group of dioxygenases called C2,β-oxidases (GA2ox) is also important in maintaining active gibberellins pool. These enzymes transform active GA and their precursors to inactive forms by hydroxylating the molecule at C2,β position [29,35,36]. In addition to C2,β-oxidase, deactivation of gibberellins in rice plants may involve EUI epoxidase (Elongated Uppermost Internode phenotype) from the P450 monooxygenases family [28,29], and in Arabidopsis methyltransferase (GAMT1 and GAMT2, Gibberellin Methyl Transferases 1, 2) may be involved [37].…”
Section: Growth Response In Mutant Plants Deficient In Gibberellin Bimentioning
confidence: 99%